Co-inhibition of Notch and NF-κB Signaling Pathway Decreases Proliferation through Downregulating IκB-α and Hes-1 Expression in Human Ovarian Cancer OVCAR-3 Cells - Majidinia, M.; Alizadeh, E.; Yousefi, B.; Akbarzadeh, M.; Mihanfar, A.; Rahmati-Yamchi, M.; Zarghami, N. (Drug Research, 2017)
Background: Ovarian cancer is one of the most lethal gynecological malignancies and numerous changes in signaling cascades are involved in the initiation and progression of ovarian cancerous cells. Here, we investigated the role of NF-κB and Notch pathways inhibition on human ovarian cancer OVCAR-3 cells proliferation and IκB-α and Hes-1 expression as 2 key genes in these pathways regulation.Methods: The effects of Bay 11-7085 and DAPT, NF-κB and Notch pathways specific inhibitors, on cell proliferation were evaluated using MTT assay. In addition, the cells were transfected by Notch and IKK-β siRNAs. mRNA and protein levels of target genes were measured by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blot after 48 h incubation with inhibitors and siRNAs.Results: Bay 11-7085 and DAPT significantly decreased the cell proliferation OVCAR-3. IκB-α and Hes-1 mRNA levels decreased to 5 or 3% and 6% or 2% after treatment with Bay 11-7085 or DAPT, respectively (p<0.05). We also found that combination treatment exert a more potent effects on the expression of these gene (p<0.05). Moreover, siRNA transfection caused a significant reduction in IκB-α and Hes-1 mRNA levels (p<0.05). In the protein level, OVCAR-3 cell treatment with both chemichal inhibitors and specific siRNA cause a significant decrease in the expression of target genes (p<0.05)Conclusion: Our findings suggest that inhibition of NF-κB and Notch signaling pathways can effectively reduce OVCAR-3 cells proliferation. Therefore, pharmacological targeting of the NF-κB and Notch signaling pathway could be a promising future treatment of ovarian cancer.
Keywords: NF-κB signaling pathway; IκB-α; notch signaling pathway; OVCAR-3 cells